(Fe, Ni, Co)9S8@CS catalyst decorated on N‐doped carbon as an efficient electrocatalyst for oxygen evolution reaction. (10th October 2021) - Kim, Youngkwang; Karuppannan, Mohanraju; Lee, Dohyeon; Bae, Hyo Eun; Luong, Quang Thien; Kang, Sun Young; Sung, Yung‐Eun; Cho, Yong‐Hun; Kwon, Oh Joong
Summary: Fe, Ni, and Co and their alloys are widely studied for oxygen evolution reaction and hydrogen evolution in electrocatalytic water splitting under alkaline conditions, and their pentlandite sulfide was found to enhance the catalytic activity for the reactions. In this study, the synthesis of pentlandite sulfide of Fe, Ni, and Co was tried by a ball milling and subsequent pyrolysis. It was proved that the ball milling method is a promising way for a pentlandite formation and simultaneous carbon encapsulation. An aniline monomer played a role of carbon source for carbon encapsulation, and ammonium persulfate provided sulfur for a sulfide formation. Three kinds of compounds were synthesized by varying the Ni/Co ratio, and their structural characteristics and electrochemical activity were investigated and compared each other. X‐ray diffraction patterns showed that they consisted of pentlandite sulfide and metal alloy phase. Transmission electron microscopy revealed that nanoparticles enwrapped by carbon shell were uniformly distributed on N‐doped carbon. Electrochemical activity was studied under alkaline condition, and the overpotential of 260 mV at 10 mA/cm 2 was obtained in 1 M KOH solution for oxygen evolution reaction. After 500 cycles, the overpotential increased slightly to 310 mV. From this study, it was revealed that the electrochemical activity of (Fe, Ni, Co)9 S8 depends on structural parameters not elemental composition. Abstract : Trimetallic pentrladite sulfide of Fe, Ni and Co enwrapped with carbon layer was successfully synthesized by a solid‐state copolymerization and a follwoing pyrolysis. It was revealed that electrochemical activity of (Fe, Ni, Co)9 S8 depends on structural parameters not elemental composition and that carbon shell is effective for protecting the catalyst. The catalyst showed the overpotential of 260 mV at 10 mA cm ‐2 for oxygen evolution reaction and demonstrated the stability over 500 cyclic voltammetry cycles.